Transvaginal Shear Wave Elastography for Assessment of Endometrial and Subendometrial Pathologies: A Prospective Pilot Study. (1st March 2021) - Vora, Zainab; Manchanda, Smita; Sharma, Raju; Das, Chandan Jyoti; Hari, Smriti; Mathur, Sandeep; Kumar, Sunesh; Kachhawa, Garima; Khan, Maroof Ahmad
Abstract : Objective: To assess the role of shear wave elastography (SWE) in characterizing different endometrial and subendometrial pathologies. Methods: Seventy‐three women with pathologically proven endometrial and subendometrial pathologies were enrolled in this prospective study and assessed with transvaginal SWE. The elasticity values (in kiloPascals), and the ratio of mean elasticity of the endometrial lesion to myometrial elasticity (E/M ratio) were compared in different pathologies. Results: There was a statistically significant difference ( P < .001) in the mean, minimum, and maximum elasticity of the pathologies as well as the E/M ratio ( P < .00001). In the analysis of the subgroups, the mean elasticity of endometrial polyp was statistically significantly lower than other subgroups ( P < .01), while submucosal leiomyoma and focal adenomyoma had significantly higher values than other subgroups ( P < .01). No statistically significant difference was noted in the mean elasticity of carcinoma and hyperplasia ( P‐ .19). Conclusion: SWE is a potential adjunct to ultrasound that provides an additional paradigm to characterize endometrial and subendometrial masses.